2010
DOI: 10.1117/1.3481141
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of dihydroartemisinin–induced apoptosis through reactive oxygen species–mediated caspase-8 activation and mitochondrial pathway in ASTC-a-1 cells using fluorescence imaging techniques

Abstract: Abstract. Dihydroartemisinin ͑DHA͒, a front-line antimalarial herbal compound, has been shown to possess promising anticancer activity with low toxicity. We have previously reported that DHA induced caspase-3-dependent apoptosis in human lung adenocarcinoma cells. However, the cellular target and molecular mechanism of DHAinduced apoptosis is still poorly defined. We use confocal fluorescence microscopy imaging, fluorescence resonance energy transfer, and fluorescence recovery after photobleaching techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Based on our previous study that mitochondrial apoptosis pathway plays an important role in both DHA-and ARTS-induced apoptosis, especially DHA induced apoptosis via both Bax-and caspase-9-dependent pathway [9,10], and ARTS induced apoptosis largely via a Bakmediated and caspase-independent pathway (unpublished data), we started the study of ARTE to find some difference among their pro-apoptotic mechanism in human lung adenocarcinoma (ASTC-a-1) cells. Our results reveal that ARTE induces caspase-dependent apoptosis without Bid cleavage and cytochrome c release from mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous study that mitochondrial apoptosis pathway plays an important role in both DHA-and ARTS-induced apoptosis, especially DHA induced apoptosis via both Bax-and caspase-9-dependent pathway [9,10], and ARTS induced apoptosis largely via a Bakmediated and caspase-independent pathway (unpublished data), we started the study of ARTE to find some difference among their pro-apoptotic mechanism in human lung adenocarcinoma (ASTC-a-1) cells. Our results reveal that ARTE induces caspase-dependent apoptosis without Bid cleavage and cytochrome c release from mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage of endoperoxide bridge in ARTE induces the generation of organic free radicals which disturb the natural oxidation and reduction equilibrium in cells, and leads to an increase of reactive oxygen species (ROS) that can induce caspasedependent apoptotic cell death in HeLa-60 cells [6,7] and injury in a variety of mammalian cells such as lung cancer A549 cells [8]. Our recent studies showed that DHA induced ROS-dependent apoptosis via caspase-8 activation and mitochondrial pathway in ASTC-a-1 cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of ROS in the apoptosis induced by Dihydroartemisinin investigated in cancer cells [18]. Lu et.al demonstrated that Dihydroartemisinin induced apoptosis via ROS formation in ASTC-a-1 cells [18]. In this study, it has been shown that Dihydroartemisinin induced ROS formation in A-431 human skin cancer cells.…”
Section: Discussionmentioning
confidence: 69%
“…Lu et al demonstrated that Dihydroartemisinin induced apoptosis in human lung adenocarcinoma cells by upregulation of Bax protein family [17].ROS are involved at several different points in the apoptotic pathway, including loss of mitochondrial membrane integrity with the attendant release of mitochondrial apoptogenic factors, intracellular caspase activation, and DNA damage [26,27]. The role of ROS in the apoptosis induced by Dihydroartemisinin investigated in cancer cells [18]. Lu et.al demonstrated that Dihydroartemisinin induced apoptosis via ROS formation in ASTC-a-1 cells [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation